A suitable (wide-range + linear) temperature sensor based on Tm3+ ions. Issue 1 (December 2017) - Zanatta, A.; Scoca, D.; Alvarez, F.
Abstract Future advances in the broad fields of photonics, (nano-)electronics or even theranostics rely, in part, on the precise determination and control, with high sensitivity and speed, of the temperature of very well-defined spatial regions. Ideally, these temperature-sensors (T-sensors) should produce minimum (or no) disturbance in the probed regions, as well as to exhibit good resolution and significant dynamic range. Most of these features are consistent with the sharp and distinctive optical transitions of trivalent rare-earth (RE3+ ) ions that, additionally, are susceptible to their local environment and conditions. Altogether, these aspects form the basis of the present work, in which we propose a new T-sensor involving the light emission of trivalent thulium ions (Tm3+ ) embedded into crystalline TiO2 . The optical characterization of the TiO2 :Tm3+ system indicated a Tm3+ -related emission at ~676 nm whose main spectral features are: (1) a temperature-induced wavelength shift of −2.2 pm K−1, (2) a rather small line-width increase over the ~85–750 K range, and (3) minimum data deconvolution-processing. The study also included the experimental data of the well-established pressure- and T-sensor ruby (Al2 O3 :Cr3+ ) and a comprehensive discussion concerning the identification and the excitation-recombination mechanisms of the Tm3+ -related transitions.